Metafoor, teologie, verbeelding: "n Postmoderne beskouing - Beukes, C. J. (Hervormde teologiese studies, 1993)
Metaphor, theology, imagination ; A postmodern perspective The quintessence of the hypothesis stated in this article is the coexistence between and symbiotic interrelationship of metaphors, contemporary theology and the imagination. This interrelation should be regarded as a postmodern phenomenon, and should be interpreted accordingly. The anti-atomistic, anti-modernistic and non-doctrinal nature of the above constitutes the hypothesis. Any theology which disregards this perspective will progressively be identified as a fatal and selfdestructive hermeneutical activity, by the postmodern condition itself. This hypothesis has far-reaching implications for contemporary theological reflection, which are stipulated by means of an interpretive conclusion.